Determinan Hipertensi pada Lansia di Puskesmas Sidomulyo Kota Pekanbaru - Liva Maita (Jurnal Kesehatan, 2017)
Hypertension is a condition in which a person has an elevated blood pressure above normal which is indicated by systolic number ≥140 mmHg and diastolic ≥ 90 mmHg. Based on the Health Profile of Riau Province in 2010 the incidence of hypertension ranks first of 10 most common diseases, namely 27.3%. The purpose of this study to determine the determinant factors of hypertension in elderly in Puskesmas Sidomulyo Pekanbaru. The type of this research is quantitative analytical research with cross sectional design. Population amounted to 4.101 people with a sample of 176 people.Teknik sampling used purposive sampling. Data analysis in this research is multivariate analysis using multiple logistic regression test. The results of this study indicate that there is a correlation of hypertension history with hypertension occurrence with p value 0,001 (<0,05), OR 95% CI 13,3 (5,74 to 30,93). Health workers are expected to perform routine blood pressure checks on the elderly, providing information, education and health promotion about hypertension.